ANALISIS FASILITAS, TARIF DAN KUALITAS PELAYANAN PENGGUNAAN TRANSPORTASI BUS RAPID TRANS (BRT) DI KOTA SEMARANG (Jurnal Riset Manajemen dan Akuntansi, 2023)
The purpose of this study was to analyze the influence of service quality, fares, facilities on the decision to use the Semarang Bus Rapid Trans (BRT) service. The problems faced are in the form of a lack of pedestrian facilities and the use of bicycles, less comfortable and safe shelters or bus stops, no digital or non-digital information media for notifications regarding the arrival of buses or the routes traversed by the Semarang BRT. In addition, the fare factor also plays an important role in public transportation, affordable fares for all people and the many benefits that can be obtained will increase public interest in using public transportation. This research uses descriptive analysis method with a quantitative approach. The population and samples were taken from 100 passengers of Semarang BRT. Data analysis was carried out by grouping data based on variables and types of respondents, tabulating data based on variables from all respondents, presenting data for each variable studied. The results of the study are that tariffs have a positive value and have a significant effect on the decision to use BRT services. Furthermore, the facility has a positive value and has a significant effect on the decision to use BRT services. The conclusion is that service quality is in a fairly high category in driving decisions to use Semarang BRT services. besides that the facility is included in the fairly strong category in the decision to use BRT Semarang services